Implementing Global Citizenship Education in Islamic Boarding Schools - Rasyid, Mufti (Proceeding International Conference on Education, 2023)
Education can transform the way we think and act to build more peaceful, tolerant and inclusive societies. In this globalized and interconnected world, global citizenship education (GCED) is urgently required to develop students’ values, soft skills and attitudes for social transformation. Unfortunately, GCED is not well known and not been implemented seriously in Indonesia, especially in pesantren (Islamic boarding schools). In fact, pesantren as prominent element of Islamic education has big responsibilities to promote the spirit of multiculturalism and social transformation for better world. This is in line with the spirit of fiqih peradaban (fiqh of civilization) which is brought by pesantren. This article aims to propose conceptual idea on global citizenship in pesantren and method to implement is using instructional technology. Using descriptive qualitative method and utilizing literature review, this article tried to answer this following question: “How is the design of global citizenship education in pesantren?” The result concluded that to design GCED, a comprehensive curriculum should be designed to integrate cognitive, social-emotional and behavior aspects of GCED with the value and principles pf pesantren. Beside of that, the use of instructional technology like audio-visual media, internet and artificial intelligence (AI) should be maximized to create advanced results.